A295 FUCOSE AVAILABILITY AND ITS UTILIZATION IMPACT IN VIVO ENTERIC PATHOGEN VIRULENCE. (1st March 2018) - Allaire, J M; Bhullar, K; Crowley, S M; Stahl, M; Yang, H; Verdu, E; YU, H; Vallance, B
Abstract: Background: Attaching and effacing (A/E) pathogens such as Enterohemorrhagic E. coli (EHEC) are important causes of diarrheal disease worldwide. Interestingly, little is known about how these bacteria obtain key nutrients, and whether these nutrients modulate pathogen colonization and gut infection. For example, fucose is an important sugar and bacterial food source cleaved from host glycans found on the intestinal mucosal surface via the actions of commensal microbes expressing fucosidase enzymes. Interestingly, although the mouse A/E pathogen Citrobacter rodentium does not itself express a fucosidase, recent studies have found that it and EHEC use a fucose sensing system to modulate their pathogenicity in vitro . At present, it is unclear what role fucose metabolism may play in A/E pathogen virulence and metabolism in vivo . To address this, we focused on C. rodentium enzyme L-fuculose kinase (encoded by the fucK gene), which plays a key role in the L-fucose metabolic pathway and fucose utilization as a food source. Aims: We investigated the roles of fucose and the enzyme L-fuculose kinase in controlling C. rodentium pathogenesis. Methods: Wildtype (WT) and Δ fucK C. rodentium were used for in vitro assays (type three secretion, growth and adhesion assays) and for in vivo infection. C57Bl/6 mice were infected either separately, or with both C. rodentium strains at a dose of 10^8 colony forming units. In some infections, mice were pretreated with streptomycin (20mg 24h pre-infection) or were fed fucose (200ul of 25mM L-fucose 2x/day). Bacterial burdens, pathology score and competitive assay were assessed on day 6 post-infection. Results: In vitro virulence assays identified no significant differences between Δ fucK and WT C. rodentium regarding type three secretion, growth or adherence to cultured epithelial cells. Moreover, both WT and Δ fucK C. rodentium readily colonized the intestines of mice either pretreated (or not), with streptomycin, with pathogen burdens, localisation and histological pathology scores similar between the two strains. In contrast, simultaneous infection by both strains (competitive assay) within the same mice revealed the ΔfucK strain was significantly impaired when competing with WT C. rodentium (no streptomycin). In contrast, ΔfucK was able to equally compete with WT C. rodentium when streptomycin pretreatment was given to deplete commensal bacteria. Feeding fucose to these streptomycin treated mice again reduced the ability of the ΔfucK strain to compete with WT C. rodentium . Conclusions: These results indicate that the fucK-dependent fucose metabolic pathway promotes but is not essential to C. rodentium pathogenesis. Moreover these findings suggest that commensal microbes play a key role in controlling fucose availability in the gut, and thereby impact A/E pathogen metabolism and virulence. Funding Agencies: CCC, CIHRNSERC, FRQS